PENGELOLAAN MUTU PEMBELAJARAN DI MTs NEGERI KARANGANYAR - TUKIMIN , TUKIMIN (2011)
The Purposes of this research are to the describe the characteristic management of quality learning process, describe characteristic management of output quality learning, and so describe characteristic support and resistance factors of learning quality management at Karanganyar Islamic Junior High School. This research applies qualitative approach executed in Karanganyar Islamic Junior High School. Sources of informan at this research is Headmaster, teacher, student and school committee. Data collecting method applies interview, observation, and documentation. Analysis technique applies qualitative analysis that is reduction of data, presentation of data and withdrawal conclusion. In qualitative research there are some way to increase validity of research data, that is: triangulation, confirmability, and dependability, The result of research indicates that management characteristic quality of study process in Karanganyar Islamic Junior High School is started with existence of workshop in the beginning of school year as a planning, in its management, headmaster with teacher studies about KTSP, syllabus and also RPP as well as KKM. Management characteristic quality of output done by Karanganyar Islamic Junior High School is shown by increasing student average value, increases percentage of pass, increases student continuing to the next education ladder, increases student continuing to favorite school, and supplies the student with efficiency of life like sewing, computer, and gardens. Supplementary factor characteristic for example coming from student old fellow support from and also school committee also stands in management quality of this study. The factor becoming the resistor is characteristic each element personnel of different school. Firstly is the teacher character. The second is student characteristic. Pass anticipation to both factors above which has been planned by the side of school hence supplementary factor can close over and minimize of the resistor factor.